THE SYMBOLIC AND IDEOLOGICAL SYSTEM IN RUBEN HOVSEPYAN'S NOVEL ―ARMENIAN DISTRICT - Zargaryan, A. (SUSh Scientific Proceedings, 2025)
The political and social radical changes that took place in the Soviet Union after 1954 had their own impact, especially in art and culture. The overcoming of the cult of the individual and the new realities had their mark in the Soviet-Armenian culture as well. Literature was also not left out of that process. The period of revaluation also brought to light those literary themes that were forbidden. The forbidden topics could already be addressed, but at the expense of maintaining a number of creative nuances. It was during that period that Armenian literature gained new momentum. The new breath was felt in both prose and verse works. The prose of the 1970s was not left out of that process either. Literary critic Sevak Arzumanyan gives a general idea of the prose of that period, who presents the development path of prose, the authors in the square, the literary-artistic value they created and the development perspectives. In that period, the novelist Ruben Hovsepyan also appeared, who spoke about the problems of the Armenian people, national ideas, and reflections of the Armenian people in his novel ―Armenian district‖. The novel ―Armenian district‖ is a unique story about the fate and historical reality of Armenians. Emphasizing the historical reality, Ruben Hovsepyan gives the story of the resettlement of immigrants after the genocide and their rediscovery in Eastern Armenia. This is another story of an Armenian emigrant, where the writer artistically records the historical fact. The transition from one homeland to another was done with a heavy psychological and physical struggle. The study focuses on the symbolic and ideological system of the novel, which has a national tone. It is at this point that the artistic value of the special novel lies.